OPTIMASI KOMPOSISI MAKANAN UNTUK PENDERITA ANEMIA MENGGUNAKAN METODE VARIABLE NEIGHBORHOOD SEARCH - Muhammad Misdram; Adi Cahyono (STMIK YADIKA BANGIL, 2021)
Abstract: Lack of blood or anemia is a condition when the body lacks healthy red blood cells or when red blood cells do not function properly. Anemia is defined as a low concentration of hemoglobin (Hb) in the blood (WHO, 2015). Anemia is one of the problems with anemia that commonly occurs when the number of erythrocytes is less than normal or due to low hemoglobin concentrations in the blood (Depkes, 2008). One of the efforts to live a healthy life in patients with anemia is to pay attention to the consumption of healthy foods as needed. The composition of food by paying attention to the level of iron content in food can be done using the Variable Neighborhood Search (VNS) method. The data used in this study are 100 food data and data on nutritional needs according to age and gender. VNS has several stages, namely after generating the initial solution then doing the shaking stage, local search. The test results show that the average fitness results are seen from the criteria values. The number of local searches that are too many does not guarantee a solution with the best fitness, but a large number of local searches can provide wider search opportunities. The results of the study were in the form of optimizing the composition of food that had been selected by the patient by approaching the nutritional needs of the anemic patient.Keywords: Anemia, Food Composition, Variable Neighborhood Search